Attenuation ofβ-Amyloid-Induced Oxidative Cell Death by Sulforaphane via Activation of NF-E2-Related Factor 2 - Chan Lee; Gyu Hwan Park; Seong‐Ryong Lee; Jung‐Hee Jang (2013)
β-amyloid peptide (Aβ), a major component of senile plaques, plays important roles in neuropathology of Alzheimer's disease (AD). An array of in vitro and in vivo data indicates that Aβ-induced neuronal death is mediated by oxidative stress. In this study, we aimed to investigate effects of sulforaphane (SUL), an isothiocyanate in cruciferous vegetables, on Aβ-induced oxidative cell death in SH-SY5Y cells. Cells treated with Aβ(25-35) exhibited decreased cell viability and underwent apoptosis as determined by MTT assay and TUNEL, respectively. Aβ(25-35)-induced cytotoxicity and apoptotic characteristics such as activation of c-JNK, dissipation of mitochondrial membrane potential, altered expression of Bcl-2 family proteins, and DNA fragmentation were effectively attenuated by SUL pretreatment. The antiapoptotic activity of SUL seemed to be mediated by inhibition of intracellular accumulation of reactive oxygen species and oxidative damages. SUL exerted antioxidant potential by upregulating expression of antioxidant enzymes including γ-glutamylcysteine ligase, NAD(P)H:quinone oxidoreductase-1, and heme oxygenase-1 via activation of NF-E2-related factor 2(Nrf2). The protective effect of SUL against Aβ(25-35)-induced apoptotic cell death was abolished by siRNA of Nrf2. Taken together, the results suggest that pharmacologic activation of Nrf2 signaling pathway by SUL might be a practical prevention and/or protective treatment for the management of AD.